Asymptomatic Carrier State as a Measure of Information Uncertainty of the Novel Coronavirus Infection - Kiladze, Andrey Bondoevich (Journal of Liaquat University of Medical & Health Sciences, 2021)
This case report describes entropy based on statistics of the novel coronavirus infection in the Russian Federation. Entropy (in bits) determined on the basis of the ratio of patients with clinical manifestations of the disease and asymptomatic carrier state, increased from 0.7219 by April 1, 2020, when the ratio of such patients was 4/5 to 1/5, to 0.8813 by April 14, 2020, when the ratio of the two groups of patients was 7/10 to 3/10. On May 3, 2020, the ratio of the two groups leveled off, reaching ½ to ½, so the entropy was 1.0000. An analysis of the data from April 19, 2020 to June 1, 2020 allowed us to clarify the average proportion between patients with and without symptoms, which is 14/25 to 11/25 with a certain bias towards patients with clinical manifestations of the novel coronavirus infection, and the entropy for this ratio is 0.9896. We found a transformation of entropy of the novel coronavirus infection which is explained by different proportions of patients with and without symptoms of the disease. KEYWORDS: The novel coronavirus infection (COVID-19), Asymptomatic patients, Symptomatic patients, Information theory, Entropy analysis, Alternative signs, Health statistics.